Serum microRNA-125a-5p as a potential biomarker of HCV-associated hepatocellular carcinoma - Oura, Kyoko (Oncol Lett, 2019)
During diagnosis of early stage hepatocellular carcinoma (HCC), single or small lesions are difficult to identify using screening ultrasonography, and conventional tumor markers are frequently negative. MicroRNAs (miRNAs) are small non-coding RNAs that suppress the translation of target mRNAs and exert significance as biomarkers. The aim of the present study was to use samples of patients with HCC and those with other liver diseases caused by hepatitis C virus (HCV) infection to investigate the expression profile of serum miRNAs, and identify a miRNA that can serve as a HCC biomarker. Initially, changes in 2,555 miRNAs between pre- and post-curative treatment serum from 12 patients with early stage HCC were examined using microarray analysis. The serum levels of miR-125a-5p in 40 individuals with HCV-associated chronic hepatitis (CH), liver cirrhosis (LC) or HCC were measured using reverse transcription-quantitative polymerase chain reaction, and 5 miRNAs, including miR-125a-5p, miR-423-5p, miR-1247, miR-1304 and miR-3648, were identified to be downregulated following curative treatment in patients with HCC. Among these, miR-125a-5p was identified to be similarly decreased following treatment in all patients. Additionally, the expression levels of miR-125a-5p were significantly upregulated in patients with HCC in the early and advanced stages of disease, compared with patients with CH or LC (P<0.05). Serum miR-125a-5p fluctuates depending on the presence of HCC, and may serve as a noninvasive biomarker to aid in diagnosing early carcinogenesis in HCV-associated chronic liver diseases.